2011
DOI: 10.1007/s00702-011-0746-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the calcineurin inhibitor FK506 on K+–Cl− cotransporter 2 expression in the mouse hippocampus after kainic acid-induced status epilepticus

Abstract: Calcineurin (CaN)-mediated excitotoxicity impairs γ-aminobutyric acid (GABA) transmission and induces neuronal apoptosis. Ca(2+)-dependent K(+)-Cl(-) cotransporter 2 (KCC2) participates in GABAergic inhibitory transmission. However, the mechanism by which CaN mediates GABA receptor-mediated KCC2 in seizures is not fully understood. In the present study, we investigated the altered expression of KCC2 and the effects of the CaN inhibitor FK506 on KCC2 expression in the mouse hippocampus following kainic acid (KA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…In the chemically induced models of SE, there is some disagreement in the literature at time points greater than 1 h after SE induction. Kainate‐induced SE in mice caused a marked increase in KCC2 total protein levels at 2, 6, and 24 h prior to returning to basal levels at the 48‐h time point in the hippocampus (Shin et al., 2012). This study also found a small decrease in the expression of NKCC1 at 6 h. Similarly, pilocarpine‐induced SE caused a transient up‐regulation of KCC2 mRNA levels at the 6‐h time point (Zhu et al., 2012).…”
Section: Chloride Homeostasis and Refractory Seizuresmentioning
confidence: 99%
“…In the chemically induced models of SE, there is some disagreement in the literature at time points greater than 1 h after SE induction. Kainate‐induced SE in mice caused a marked increase in KCC2 total protein levels at 2, 6, and 24 h prior to returning to basal levels at the 48‐h time point in the hippocampus (Shin et al., 2012). This study also found a small decrease in the expression of NKCC1 at 6 h. Similarly, pilocarpine‐induced SE caused a transient up‐regulation of KCC2 mRNA levels at the 6‐h time point (Zhu et al., 2012).…”
Section: Chloride Homeostasis and Refractory Seizuresmentioning
confidence: 99%
“…KA injection activates both astrocytes and microglia related to cell apoptosis and increases inflammatory cytokines in damaged hippocampal neuronal cells [ 3 ]. KA-induced blood-brain barrier (BBB) leakage is associated with ionic imbalance and nuclear factor-κB (NF-κB) activation [ 4 5 ]. Thus, inhibition of neuroinflammation and neurovascular breakdown may be critical to protect against seizures-induced neuronal death.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Recent papers showed that the brain edema induced by BBB leakage in seizures is associated with nuclear factor-kB (NF-kB) activation and ionic imbalance. 8,9 Thus, controlling the severity of neuroinflammation and BBB leakage may be critical to protect against seizure-induced neuronal death.…”
mentioning
confidence: 99%